2004
DOI: 10.1021/ma048159+
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Melting Behavior of Poly(3-butylthiophene), Poly(3-octylthiophene), and Poly(3-dodecylthiophene)

Abstract: The crystallization and melting behavior of poly(3-butylthiophene) (P3BT), poly(3-octylthiophene) (P3OT), and poly(3-dodecylthiophene) (P3DDT) were studied. The equilibrium melting temperatures (T m 0) of these polymers were measured and resulted equal to 321, 230, and 175 °C for P3BT, P3OT, and P3DDT, respectively. The crystallization kinetics was evaluated by the Avrami equation:  it proceeds by heterogeneous nucleation with one-dimensional linear growth (n = 1.1−1.8). The effects of the length of the alkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(184 citation statements)
references
References 34 publications
14
168
1
Order By: Relevance
“…Along the same line, Causin et al reported that P3DDT is crystallizing faster than poly(3-butylthiophene) because of the increased molecular mobility in the melt as the side-chain length increases. 48 This explains also the observation of a lower overall crystallinity in as spin-coated layers of P3ATs for shorter side chains. This limited molecular mobility may also account for the lower crystallinity in as spin-coated P3AT films with the shortest side chains.…”
Section: Methodsmentioning
confidence: 78%
“…Along the same line, Causin et al reported that P3DDT is crystallizing faster than poly(3-butylthiophene) because of the increased molecular mobility in the melt as the side-chain length increases. 48 This explains also the observation of a lower overall crystallinity in as spin-coated layers of P3ATs for shorter side chains. This limited molecular mobility may also account for the lower crystallinity in as spin-coated P3AT films with the shortest side chains.…”
Section: Methodsmentioning
confidence: 78%
“…With regards to these observations, the relative crystallinities of the terpolymers were compared quantitatively by estimating their heat of crystallization (∆Hc). [57][58][59] The ∆Hc values of the terpolymers increased remarkably from 5.8 (P1) to 16.2 J/g (P5) with increasing Se content, indicating a remarkable increase in the crystallinity. These significant differences in the crystalline behaviors of the terpolymers could affect their electrical properties (i.e., charge mobility) as well as their solubility in the solvent and their miscibility with fullerene acceptors.…”
Section: Resultsmentioning
confidence: 97%
“…Moderate crystallinity is usually observed when P3HT films are subjected to isothermal crystallization after melting, presumably because of the limited mobility of polymer chains in the rigid amorphous phase. 61 A number of groups have investigated the growth and crystallization of P3HT from solution. The motivation of these studies was to decouple the crystallization mechanism, which should be slow for improved crystal perfection, from the rather fast thin film processing as in the case of spin coating.…”
Section: Controlling Nucleation and Growthmentioning
confidence: 99%